Slow motion of a rotating circular cylinder through a micropolar fluid - Moosaie, A.; Atefi, G. (Archives of Mechanics, 2008)
Presented is an analytical solution to creeping flow of a micropolar fluid past a rotating circular cylinder of infinite length in spanwise direction. The solution is decomposed into two parts; first, the flow past a stationary circular cylinder is solved by the use of matched asymptotic expansions method. Afterwards, the rotation of a circular cylinder in a stationary ocean of a micropolar fluid is investigated. Due to linearity of the governing equations, the principle of superposition is then recalled to construct the desired flow field. Ultimately, several kinematic and kinetic quantities of the flow are studied by the use of the obtained closed-form analytical solution.